Using sighting records to infer extinction in three endemic A rgentinean marsupial frogs - Akmentins, Mauricio Sebastián (2011)
Three species of marsupial frogs of the genus Gastrotheca are at the forefront of amphibian conservation concern in Argentina. Most of the data available on these amphibian species in the country are in the form of museum collections. In this study, we use the recent rediscovery of G. gracilis to test the applicability of a series of probabilistic methods and a trend analysis to analyse the sighting records in the marsupial frog species of Argentina, and to assess the probability that G. christinani and G. chrysosticta are still extant. The results suggest that the two marsupial frog species are still extant, but probably declining. Based on these results, we suggest as a precautionary measure to raise the actual conservation status of these marsupial frog species to Critically Endangered.